MEASURING PUBLIC EXPENSES WITH WORKFORCE IN FIGHTING FOREST FIRE - da Silva, Elaine Cristina Gomes; Fiedler, Nilton Cesar; Ferreira, Fabio Silva; Lobato, Lucas José Teodoro; Antunes da Silva, Gabriel Mancini; Das neves, Felipe Patrício (Floresta, 2020)
Measuring public expenses with workforce in fighting forest fire. The frequency of forest fires and the lack of investment in public institutions arising from the current Brazilian economic crisis, emerges the difficulty of competent institutions in managing resources due to the increasing number of fires, mainly the labor. The objective of this work was to measure the expenses with labor in the combats against forest fires in Public Conservation Units by comparing it with the labor with prevention. This exploratory, documentary and ex post facto study was prepared based on documents and reports from public institutions involved in fighting a major fire in a Biological Reserve in the State of Espírito Santo. The data were analyzed according to the participating institutions, number of participants, positions, value of remunerations and days worked. To measure the average daily expenditure on different remunerations, an accounting model was developed, using the values of the remunerations for the year in which the fire occurred. In the end, it could be concluded that, for every 124.3 hectares burned, 110 individuals worked per day, the majority were military personnel at the beginning of their careers and that the expenditure on public labor employed in combat, both in quantity and remuneration, was much higher than the labor with the temporary hiring of firefighters.